Highly acid-resistant glass powder, method for preparing same, and use thereof

CN122958067APending Publication Date: 2026-10-23SHANGHAI WEIDELUO NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611384732.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种高耐酸玻璃粉及其制备方法和应用,旨在解决现有光伏银浆用玻璃粉耐酸性弱、烧结性能与耐酸性能难以兼顾、电极界面导电性能不佳的技术问题

Benefits of technology

本发明以TeO2-Bi2O3-B2O3基玻璃粉作为初始体系,对玻璃粉各组分进行调控,组分配比可调范围宽,可根据实际需求灵活选择,并兼容不同类型的功能性添加剂,具有优异的配方适配性与工艺窗口宽容度,适用于多种光伏银浆对玻璃粉的差异化需求;玻璃粉配方体系软化温度适配太阳能晶硅电池常规烧结工艺,无需高温烧结,有效避免硅片热损伤;结合可控晶化改性、二氧化钛包覆双重改性手段,形成双重防护结构,有效抵御光伏组件服役过程中胶膜等降解产生的醋酸侵蚀,抑制玻璃相腐蚀破坏与电极界面失效,大幅降低电池长期功率衰减幅度,显著延长光伏组件使用寿命;同时能够协同优化玻璃粉界面润湿性和溶银能力,促进银粉均匀分散与银硅的冶金结合,降低界面接触电阻,减少光电复合损耗,有效提升太阳能晶硅电池的光电转换效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of glass powder for photovoltaic silver paste, and provides a high-acid-resistance glass powder, a preparation method and application thereof.The preparation method comprises the following steps: mixing oxide raw materials to obtain mixed powder; sequentially performing melting, quenching and crushing on the mixed powder to obtain amorphous glass micro powder; performing crystallization treatment on the amorphous glass micro powder to obtain crystallized glass powder; and forming a titanium dioxide coating layer on the surface of the crystallized glass powder by adopting a sol-gel method.The application regulates and controls each component of the glass powder, has excellent formula adaptability and process window tolerance, and does not need high-temperature sintering; in combination with controllable crystallization modification and titanium dioxide coating double modification means, the application effectively resists acetic acid corrosion caused by degradation of a gel film during service of a photovoltaic module, significantly prolongs the service life of the photovoltaic module, and cooperatively optimizes the interface wettability and silver dissolving capacity of the glass powder, promotes uniform dispersion of silver powder and metallurgical combination of silver and silicon, and reduces the interface contact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass powder technology for photovoltaic silver paste, and in particular to a high acid-resistant glass powder, its preparation method, and its application. Background Technology

[0002] Solar crystalline silicon cells rely on front and back metal electrodes to extract photoelectric energy. The glass powder in the electrode silver paste is the core functional component that connects the silver powder phase to the silicon substrate, directly determining the silver-silicon interface bonding strength, ohmic contact performance, and long-term service stability of the solar crystalline silicon cell.

[0003] Currently, the glass powder used in commercial photovoltaic silver paste mainly faces the following technical bottlenecks: While traditional lead-tellurium-based glass powders exhibit excellent sintering and wetting properties, effectively reducing silver-silicon contact resistance, their resistance to acid and alkali corrosion is weak. During long-term outdoor operation of photovoltaic modules, the acetic acid produced by the aging and degradation of encapsulating films (such as EVA) continuously erodes the glass phase inside the electrodes, leading to electrode interface peeling, a significant increase in contact resistance, and rapid power degradation of the photovoltaic modules. Existing alternative glass powder systems (such as Bi2O3-B2O3-TeO2-based glass powders) have improved environmental friendliness to some extent, but they generally suffer from performance imbalances: some have excessively high glass transition temperatures, requiring higher sintering temperatures to achieve metallurgical bonding, which can easily cause thermal damage to the silicon wafer; others, while having good sintering temperature adaptability, lack sufficient acid resistance and are unable to withstand acetic acid corrosion. Furthermore, ordinary glass powders have poor wetting and fusion capabilities with silver particles, making it difficult to form dense and continuous conductive pathways, thus limiting the improvement of photoelectric conversion efficiency and fill factor in solar crystalline silicon cells.

[0004] In summary, developing a photovoltaic silver paste-specific glass powder that is lead-free and environmentally friendly, has good sintering temperature adaptability, good silver phase wettability, and excellent aging and acid resistance is of great significance for the large-scale application of solar crystalline silicon cells. Summary of the Invention

[0005] The purpose of this invention is to provide a high acid-resistant glass powder, its preparation method, and its application, aiming to solve the technical problems of existing photovoltaic silver paste glass powders having weak acid resistance, difficulty in balancing sintering performance and acid resistance, and poor electrode interface conductivity.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing high acid-resistant glass powder, comprising the following steps: 1) Mix the oxide raw materials to obtain a mixed powder; 2) The mixed powder is sequentially melted, quenched, and crushed to obtain amorphous glass micro powder; 3) Crystallize the amorphous glass powder to obtain crystallized glass powder; 4) A titanium dioxide coating layer is formed on the surface of crystallized glass powder using the sol-gel method to obtain high acid-resistant glass powder.

[0007] Preferably, by mass fraction, the oxide raw material in step 1) comprises 5-35% Bi2O3, 5-45% B2O3, 0-50% TeO2, 0-45% PbO, 0-10% ZnO, 0-15% Al2O3, and 0-8% alkali metal oxides; The sum of the mass fractions of Bi2O3, B2O3, TeO2 and PbO is ≥60%.

[0008] Preferably, the oxide raw material further comprises functional additives, which include one or more of SiO2, MgO, CaO, BaO, SrO, Ga2O3, V2O5, P2O5 and Fe2O3.

[0009] Preferably, the melting temperature in step 2) is 800~1300℃, the melting time is 1~3h, and the heating rate to the melting temperature is 5~20℃ / min.

[0010] Preferably, the particle size D of the amorphous glass micropowder in step 2) is... 50 It is 1~2μm.

[0011] Preferably, the crystallization temperature in step 3) is 380~500℃, the crystallization time is 6~10h, and the heating rate to the crystallization temperature is 3~6℃ / min.

[0012] Preferably, the thickness of the titanium dioxide coating layer in step 4) is 10~80nm.

[0013] The present invention also provides a high acid-resistant glass powder prepared by the aforementioned preparation method.

[0014] The present invention also provides the application of the aforementioned high acid-resistant glass powder in photovoltaic silver paste.

[0015] The beneficial effects of this invention are: This invention uses TeO2-Bi2O3-B2O3-based glass powder as the initial system, and regulates the various components of the glass powder. The component ratio has a wide adjustable range, which can be flexibly selected according to actual needs, and is compatible with different types of functional additives. It has excellent formulation adaptability and process window tolerance, and is suitable for the differentiated glass powder requirements of various photovoltaic silver pastes. The softening temperature of the glass powder formulation system is adapted to the conventional sintering process of solar crystalline silicon cells, eliminating the need for high-temperature sintering and effectively avoiding thermal damage to silicon wafers. Combined with controllable crystallization modification and titanium dioxide coating dual modification methods, a dual protective structure is formed, which effectively resists acetic acid erosion caused by the degradation of the encapsulant film during the service of photovoltaic modules, inhibits glass phase corrosion and electrode interface failure, significantly reduces the long-term power decay of the battery, and significantly extends the service life of photovoltaic modules. At the same time, it can synergistically optimize the wettability and silver solubility of the glass powder interface, promote the uniform dispersion of silver powder and metallurgical bonding with silver silicon, reduce interfacial contact resistance, reduce photoelectric recombination loss, and effectively improve the photoelectric conversion efficiency of solar crystalline silicon cells.

[0016] The acid-resistant glass powder of this invention, while meeting the requirements of conventional sintering processes for photovoltaic silver paste, can significantly improve the acid resistance and interfacial bonding ability of the glass powder, thereby optimizing the photoelectric performance and long-term stability of solar crystalline silicon cells from the application end. The preparation method has controllable parameters, strong repeatability, no need for complex precision equipment, small batch performance differences, and no need for significant adjustments to existing photovoltaic silver paste preparation and cell production processes, making it highly adaptable to the industry and of great promotional value. Detailed Implementation

[0017] This invention provides a method for preparing high acid-resistant glass powder, comprising the following steps: 1) Mix the oxide raw materials to obtain a mixed powder; 2) The mixed powder is sequentially melted, quenched, and crushed to obtain amorphous glass micro powder; 3) Crystallize the amorphous glass powder to obtain crystallized glass powder; 4) A titanium dioxide coating layer is formed on the surface of crystallized glass powder using the sol-gel method to obtain high acid-resistant glass powder.

[0018] In this invention, by mass fraction, the oxide raw material in step 1) preferably comprises: Bi2O3 5-35%, more preferably 10-30%, more preferably 15-25%; B2O3 5-45%, more preferably 10-35%, more preferably 15-30%; TeO 20-50%, more preferably 5-40%, more preferably 15-30%; PbO 0-45%, more preferably 5-40%, more preferably 15-30%; ZnO 0-10%, more preferably 3-8%, more preferably 5%; Al2O3 0-15%, more preferably 2-12%, more preferably 6-10%; and alkali metal oxide 0-8%, more preferably 2-6%, more preferably 4-5%. The sum of the mass fractions of Bi2O3, B2O3, TeO2 and PbO is preferably ≥60%, more preferably ≥65%, and even more preferably ≥70%.

[0019] In this invention, the alkali metal oxide preferably comprises one or more of Li2O, Na2O and K2O.

[0020] In this invention, the oxide raw material preferably further comprises functional additives, which preferably include one or more of SiO2, MgO, CaO, BaO, SrO, Ga2O3, V2O5, P2O5, and Fe2O3. SiO2 is used to improve the strength and chemical stability of the glass network structure; MgO is used to adjust the melting temperature and thermal expansion coefficient of the glass powder; CaO is used to improve the chemical durability and crystallization stability of the glass powder; BaO is used to improve the refractive index of the glass powder and its wettability to silver particles; SrO is used to adjust the softening point of the glass and the interfacial bonding strength; Ga2O3 is used to optimize the adhesion and ohmic contact characteristics of the glass powder to the silicon substrate; V2O5 is used to optimize the electronic conductivity and sintering densification behavior of the glass powder; P2O5 is used to improve the flexibility of the glass network structure and its low-temperature sintering performance; and Fe2O3 is used to adjust the sintering characteristics and interfacial reactivity of the glass powder.

[0021] In this invention, the purity of the oxide raw material is preferably ≥99.5%, and more preferably ≥99.8%.

[0022] In this invention, the melting temperature in step 2) is preferably 800~1300℃, specifically 800℃, 830℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, or 1300℃; the melting time is preferably 1~3h, more preferably 1.5~2.5h, and even more preferably 2h; the heating rate to the melting temperature is preferably 5~20℃ / min, specifically 5℃ / min, 8℃ / min, 10℃ / min, 12℃ / min, 15℃ / min, 18℃ / min, or 20℃ / min.

[0023] In this invention, the crushing in step 2) preferably includes sequential mechanical coarse crushing and ball milling.

[0024] In this invention, the ball milling speed is preferably 400~600 r / min, more preferably 450~550 r / min, and even more preferably 500 r / min; the ball milling time is preferably 10~14 h, more preferably 11~13 h, and even more preferably 12 h; the ball-to-material ratio is preferably 2~3:1, and even more preferably 2.5:1; the dispersion medium used in the ball milling is preferably anhydrous ethanol.

[0025] In this invention, the particle size D of the amorphous glass micropowder in step 2) 50 Preferably, it is 1~2μm, more preferably 1.2~1.8μm, and even more preferably 1.4~1.6μm.

[0026] In this invention, the crystallization temperature in step 3) is preferably 380~500℃, more preferably 390~480℃, and even more preferably 420~450℃; the crystallization time is preferably 6~10h, more preferably 7~9h, and even more preferably 8h; the heating rate to the crystallization temperature is preferably 3~6℃ / min, more preferably 3.5~5℃ / min, and even more preferably 4~4.5℃ / min. Crystallization treatment can regulate and optimize the internal microstructure of the glass powder, improving the structural stability of the matrix itself.

[0027] In this invention, after the crystallization treatment in step 3) is completed, it is preferable to allow the furnace to cool naturally to room temperature to obtain crystallized glass powder.

[0028] In this invention, the thickness of the titanium dioxide coating layer in step 4) is preferably 10~80nm, specifically 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, or 80nm.

[0029] In this invention, the specific steps of the sol-gel method in step 4) preferably include: A tetrabutyl titanate solution was added dropwise to a suspension of crystallized glass powder to initiate a hydrolysis reaction.

[0030] In this invention, the mass fraction of the tetrabutyl titanate solution is preferably 10-15%, more preferably 11-14%, and even more preferably 12-13%. The dripping rate is preferably 1~2 mL / min, more preferably 1.2~1.8 mL / min, and even more preferably 1.5 mL / min; The pH value of the hydrolysis reaction is preferably 7.0-7.5, more preferably 7.1-7.4, and even more preferably 7.2-7.3; the temperature of the hydrolysis reaction is preferably 60-70℃, more preferably 62-68℃, and even more preferably 65℃; the time of the hydrolysis reaction is preferably 2-3h, more preferably 2.2-2.8h, and even more preferably 2.5h. The hydrolysis reaction time is preferably started from the end of the addition of tetrabutyl titanate solution.

[0031] In this invention, stirring is preferably performed during the hydrolysis reaction, and the stirring speed is preferably 100~500 r / min, more preferably 150~400 r / min, and even more preferably 200~300 r / min.

[0032] In this invention, after the hydrolysis reaction is completed, the glass powder is preferably filtered, washed, and dried sequentially to obtain high acid-resistant glass powder. The washing process preferably involves alternating washing with anhydrous ethanol and water. The drying temperature is preferably 100~140℃, more preferably 110~130℃, and even more preferably 120℃; the drying time is preferably 2~4h, more preferably 2.5~3.5h, and even more preferably 3h.

[0033] The present invention also provides a high acid-resistant glass powder prepared by the aforementioned preparation method.

[0034] The present invention also provides the application of the aforementioned high acid-resistant glass powder in photovoltaic silver paste.

[0035] In this invention, the photovoltaic silver paste preferably comprises photovoltaic silver paste of TOPCon solar crystalline silicon cells, photovoltaic silver paste of PERC solar crystalline silicon cells, or photovoltaic silver paste of HJT solar crystalline silicon cells.

[0036] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0037] Example 1

[0038] By mass fraction, the oxide raw materials are Bi₂O₃ 25%, B₂O₃ 12%, TeO₂ 45%, ZnO 8%, Al₂O₃ 5%, and Li₂O 5%. The purity of all oxide raw materials is ≥99.8%.

[0039] The oxide raw materials were weighed according to the above composition to obtain a mixed powder. The mixed powder was placed in a corundum crucible and placed in a muffle furnace. The muffle furnace was heated to 850°C at a rate of 6°C / min and held at 850°C for 2.5 hours to fully melt the mixed powder and obtain a clear and homogeneous glass melt. The glass melt was quickly poured into deionized water at 25°C for water quenching to obtain a solid glass preform. The solid glass preform was coarsely crushed using a roller mill and then placed in a planetary ball mill. Anhydrous ethanol was added as the dispersion medium (the mass of anhydrous ethanol was 65% of the total mass of the glass preform). Zirconia balls with a particle size range of 5-10 mm were used as the ball milling medium, with a ball-to-material ratio of 2:1. The milling was carried out at a speed of 400 r / min for 12 hours. After ball milling, the preform was dried in an 80°C oven and passed through a 200-mesh sieve to obtain a particle size D. 50 Amorphous glass powder with a particle size of 1.6 ± 0.1 μm was prepared. The amorphous glass powder was evenly spread in a tube sintering furnace and heated to 450 °C at a rate of 4 °C / min under air atmosphere, and held at 450 °C for 9 hours for crystallization treatment. After crystallization, the powder was allowed to cool naturally to room temperature in the furnace to obtain crystallized glass powder.

[0040] A 12% (w / w) tetrabutyl titanate-ethanol solution was prepared. Crystallized glass powder was dispersed in deionized water at a solid-liquid ratio of 1:4, stirred until a suspension was formed, and heated to 65°C. Then, the tetrabutyl titanate-ethanol solution was added dropwise to the suspension at a rate of 1.5 mL / min, while simultaneously adjusting the pH to 7.2 with 0.1% (w / w) ammonia. After the addition was complete, a hydrolysis reaction was carried out at 200 rpm for 2.5 h, allowing the tetrabutyl titanate to hydrolyze onto the surface of the crystallized glass powder, forming a titanium dioxide coating layer. After the hydrolysis reaction was complete, the solid product was filtered out, washed three times alternately with anhydrous ethanol and deionized water, and then dried in a 120°C constant temperature oven for 3 h. After dispersing, the product was passed through a 200-mesh sieve to obtain high acid-resistant glass powder.

[0041] The titanium dioxide coating thickness of the high acid-resistant glass powder prepared in Example 1 is 30 nm.

[0042] Example 2

[0043] By mass fraction, the oxide raw materials are PbO 40%, Bi2O3 5%, B2O3 40%, ZnO 5%, Al2O3 3%, and Fe2O3 7%. The purity of all oxide raw materials is ≥99.5%.

[0044] The oxide raw materials were weighed according to the above composition to obtain a mixed powder. The mixed powder was placed in a corundum crucible and placed in a muffle furnace. The muffle furnace was heated to 950°C at a rate of 6°C / min and held at 950°C for 1 hour to fully melt the mixed powder and obtain a clear and homogeneous glass melt. The glass melt was quickly poured into deionized water at 25°C for water quenching to obtain a solid glass preform. The solid glass preform was coarsely crushed using a roller mill and then placed in a planetary ball mill. Anhydrous ethanol was added as the dispersion medium (the mass of anhydrous ethanol was 75% of the total mass of the glass preform). Zirconia balls with a particle size range of 5-10 mm were used as the ball milling medium, with a ball-to-material ratio of 3:1. The milling was carried out at a speed of 400 r / min for 12 hours. After ball milling, the preform was dried in an 80°C oven and passed through a 200-mesh sieve to obtain a particle size D. 50 Amorphous glass powder with a particle size of 1.6 ± 0.1 μm was prepared. The amorphous glass powder was evenly spread in a tube furnace and heated to 390 °C at a rate of 6 °C / min under air atmosphere, and held at 390 °C for 7.5 h for crystallization treatment. After crystallization, the powder was allowed to cool naturally to room temperature in the furnace to obtain crystallized glass powder.

[0045] A 12.5% ​​(w / w) tetrabutyl titanate-ethanol solution was prepared. Crystallized glass powder was dispersed in deionized water at a solid-liquid ratio of 1:4, stirred until a suspension was formed, and heated to 60°C. Then, the tetrabutyl titanate-ethanol solution was added dropwise to the suspension at a rate of 1.5 mL / min, while simultaneously adjusting the pH to 7.2 with 0.1% (w / w) ammonia. After the addition was complete, a hydrolysis reaction was carried out at 200 rpm for 2 hours, allowing the tetrabutyl titanate to hydrolyze onto the surface of the crystallized glass powder, forming a titanium dioxide coating layer. After the hydrolysis reaction, the solid product was filtered out, washed three times alternately with anhydrous ethanol and deionized water, and then dried in a 120°C constant temperature oven for 3 hours. After dispersing, it was passed through a 200-mesh sieve to obtain high acid-resistant glass powder.

[0046] The titanium dioxide coating thickness of the high acid-resistant glass powder prepared in this embodiment is 43 nm.

[0047] Example 3

[0048] By mass fraction, the oxide raw materials are Bi₂O₃ 33%, B₂O₃ 30%, ZnO 5%, Al₂O₃ 15%, Ga₂O₃ 10%, and SiO₂ 7%. The purity of all oxide raw materials is ≥99.9%.

[0049] The oxide raw materials were weighed according to the above composition to obtain a mixed powder. The mixed powder was placed in a corundum crucible and placed in a muffle furnace. The muffle furnace was heated to 830°C at a rate of 6°C / min and held at 830°C for 3 hours to fully melt the mixed powder and obtain a clear and homogeneous glass melt. The glass melt was quickly poured into deionized water at 25°C for water quenching to obtain a solid glass preform. The solid glass preform was coarsely crushed using a roller mill and then placed in a planetary ball mill. Anhydrous ethanol was added as the dispersion medium (the mass of anhydrous ethanol was 55% of the total mass of the glass preform). Zirconia balls with a particle size range of 5-10 mm were used as the ball milling medium, with a ball-to-material ratio of 2.5:1. The milling was carried out at a speed of 400 r / min for 12 hours. After ball milling, the preform was dried in an 80°C oven and passed through a 200-mesh sieve to obtain a particle size D. 50 Amorphous glass powder with a particle size of 1.6 ± 0.1 μm was prepared. The amorphous glass powder was evenly spread in a tube furnace and heated to 420 °C at a rate of 4 °C / min under air atmosphere, and held at 420 °C for 8 hours for crystallization treatment. After crystallization, the powder was allowed to cool naturally to room temperature in the furnace to obtain crystallized glass powder.

[0050] A 12.5% ​​(w / w) tetrabutyl titanate-ethanol solution was prepared. Crystallized glass powder was dispersed in deionized water at a solid-liquid ratio of 1:4, stirred until a suspension was formed, and heated to 65°C. Then, the tetrabutyl titanate-ethanol solution was added dropwise to the suspension at a rate of 1.5 mL / min, while simultaneously adjusting the pH to 7.2 with 0.1% (w / w) ammonia. After the addition was complete, a hydrolysis reaction was carried out at 250 rpm for 2.5 h, allowing the tetrabutyl titanate to hydrolyze onto the surface of the crystallized glass powder, forming a titanium dioxide coating layer. After the hydrolysis reaction, the solid product was filtered out, washed three times alternately with anhydrous ethanol and deionized water, and then dried in a 120°C constant temperature oven for 3 h. After dispersing, the product was passed through a 200-mesh sieve to obtain high acid-resistant glass powder.

[0051] The titanium dioxide coating thickness of the high acid-resistant glass powder prepared in this embodiment is 45 nm.

[0052] Comparative Example 1

[0053] By mass fraction, the oxide raw materials are Bi₂O₃ 25%, B₂O₃ 12%, TeO₂ 45%, ZnO 8%, Al₂O₃ 5%, and Li₂O 5%. The purity of all oxide raw materials is ≥99.8%.

[0054] The oxide raw materials were weighed according to the above composition to obtain a mixed powder. The mixed powder was placed in a corundum crucible and placed in a muffle furnace. The muffle furnace was heated to 850°C at a rate of 6°C / min and held at 850°C for 2.5 hours to fully melt the mixed powder and obtain a clear and homogeneous glass melt. The glass melt was quickly poured into deionized water at 25°C for water quenching to obtain a solid glass preform. The solid glass preform was coarsely crushed using a roller mill and then placed in a planetary ball mill. Anhydrous ethanol was added as the dispersion medium (the mass of anhydrous ethanol was 65% of the total mass of the glass preform). Zirconia balls with a particle size range of 5-10 mm were used as the ball milling medium, with a ball-to-material ratio of 2:1. The milling was carried out at a speed of 400 r / min for 12 hours. After ball milling, the preform was dried in an 80°C oven and passed through a 200-mesh sieve to obtain a particle size D. 50 It is an amorphous glass micropowder with a particle size of 1.6 ± 0.1 μm.

[0055] Comparative Example 2

[0056] By mass fraction, the oxide raw materials are PbO 40%, Bi2O3 5%, B2O3 40%, ZnO 5%, Al2O3 3%, and Fe2O3 7%. The purity of all oxide raw materials is ≥99.5%.

[0057] The oxide raw materials were weighed according to the above composition to obtain a mixed powder. The mixed powder was placed in a corundum crucible and placed in a muffle furnace. The muffle furnace was heated to 950°C at a rate of 6°C / min and held at 950°C for 1 hour to fully melt the mixed powder and obtain a clear and homogeneous glass melt. The glass melt was quickly poured into deionized water at 25°C for water quenching to obtain a solid glass preform. The solid glass preform was coarsely crushed using a roller mill and then placed in a planetary ball mill. Anhydrous ethanol was added as the dispersion medium (the mass of anhydrous ethanol was 75% of the total mass of the glass preform). Zirconia balls with a particle size range of 5-10 mm were used as the ball milling medium, with a ball-to-material ratio of 3:1. The milling was carried out at a speed of 400 r / min for 12 hours. After ball milling, the preform was dried in an 80°C oven and passed through a 200-mesh sieve to obtain a particle size D. 50 It is an amorphous glass micropowder with a particle size of 1.6 ± 0.1 μm.

[0058] Comparative Example 3

[0059] By mass fraction, the oxide raw materials are PbO 40%, Bi2O3 5%, B2O3 40%, ZnO 5%, Al2O3 3%, and Fe2O3 7%. The purity of all oxide raw materials is ≥99.5%.

[0060] The oxide raw materials were weighed according to the above composition to obtain a mixed powder. The mixed powder was placed in a corundum crucible and placed in a muffle furnace. The muffle furnace was heated to 950°C at a rate of 6°C / min and held at 950°C for 1 hour to fully melt the mixed powder and obtain a clear and homogeneous glass melt. The glass melt was quickly poured into deionized water at 25°C for water quenching to obtain a solid glass preform. The solid glass preform was coarsely crushed using a roller mill and then placed in a planetary ball mill. Anhydrous ethanol was added as the dispersion medium (the mass of anhydrous ethanol was 75% of the total mass of the glass preform). Zirconia balls with a particle size range of 5-10 mm were used as the ball milling medium, with a ball-to-material ratio of 3:1. The milling was carried out at a speed of 400 r / min for 12 hours. After ball milling, the preform was dried in an 80°C oven and passed through a 200-mesh sieve to obtain a particle size D. 50 Amorphous glass powder with a particle size of 1.6 ± 0.1 μm was prepared. The amorphous glass powder was evenly spread in a tube furnace and heated to 390 °C at a rate of 6 °C / min under air atmosphere, and held at 390 °C for 7.5 h for crystallization treatment. After crystallization, the powder was allowed to cool naturally to room temperature in the furnace to obtain crystallized glass powder.

[0061] Comparative Example 4

[0062] By mass fraction, the oxide raw materials are Bi₂O₃ 33%, B₂O₃ 30%, ZnO 5%, Al₂O₃ 15%, Ga₂O₃ 10%, and SiO₂ 7%. The purity of all oxide raw materials is ≥99.9%.

[0063] The oxide raw materials were weighed according to the above composition to obtain a mixed powder. The mixed powder was placed in a corundum crucible and placed in a muffle furnace. The muffle furnace was heated to 830°C at a rate of 6°C / min and held at 830°C for 3 hours to fully melt the mixed powder and obtain a clear and homogeneous glass melt. The glass melt was quickly poured into deionized water at 25°C for water quenching to obtain a solid glass preform. The solid glass preform was coarsely crushed using a roller mill and then placed in a planetary ball mill. Anhydrous ethanol was added as the dispersion medium (the mass of anhydrous ethanol was 55% of the total mass of the glass preform). Zirconia balls with a particle size range of 5-10 mm were used as the ball milling medium, with a ball-to-material ratio of 2.5:1. The milling was carried out at a speed of 400 r / min for 12 hours. After ball milling, the preform was dried in an 80°C oven and passed through a 200-mesh sieve to obtain a particle size D. 50 It is an amorphous glass micropowder with a particle size of 1.6 ± 0.1 μm.

[0064] Photovoltaic silver pastes were prepared using the glass powders prepared in Examples 1-3 and Comparative Examples 1-4, respectively. The composition of the photovoltaic silver pastes, by mass fraction, was: 88% silver powder (Smet S560), 10% organic carrier, and 2% glass powder. The preparation process of the organic carrier was as follows: 30 parts by mass of diethylene glycol butyl ether acetate (DBAC), 12 parts by mass of tripropylene glycol methyl ether (TPM), 8 parts by mass of tripropylene glycol butyl ether (TPNB), 16 parts by mass of dodecyl alcohol ester (CS-12), and 9 parts by mass of diethylene glycol butyl ether (DGBE) were mixed and stirred at 500 rpm while simultaneously adding 7 parts by mass of ethyl cellulose. The mixture was then heated to 80°C and stirred at 800 rpm until clear and transparent. The temperature was then lowered to 50°C, and while stirring at 500 rpm, 6 parts by mass of benzyl silicone oil, 4 parts by mass of petrolatum, and 3 parts by mass of modified hydrogenated castor oil were added sequentially. Then, 5 parts by mass of polyamide wax powder were added, maintaining a constant temperature throughout the addition process. The mixture was then stirred at 1000 rpm until a uniform gel-like organic phase without white particles or clumps was formed; this was the organic carrier. Silver powder, the organic carrier, and glass powder were mixed and ground uniformly using a three-roll mill (fineness ≤ 5 μm) to obtain photovoltaic silver paste. The photovoltaic silver paste was printed onto the back of a TOPCon crystalline silicon cell and sintered in a tunnel sintering furnace (peak temperature 780℃) to obtain a solar crystalline silicon cell. The solar crystalline silicon cell was subjected to IV testing under standard conditions (AM 1.5G, 25℃). The acetic acid vapor accelerated aging test conditions were as follows: the solar crystalline silicon cell was placed in an 85℃ constant temperature oven, with a saturated solution (prepared from 6 mL of 10% acetic acid, 194 mL of deionized water, and 115 g of potassium chloride) placed in the oven. After aging for 24 hours, the performance degradation after aging was tested. The photoelectric performance test results are shown in Table 1.

[0065] Table 1. Photovoltaic performance test results of solar crystalline silicon cells

[0066] As shown in Table 1, the initial electrical performance data of Examples 1-3 of the present invention exhibit conversion efficiencies of 25.75-26.13% and fill factors of 82.48-86.54%, which are essentially at the same level as those of Comparative Examples 1-4 (conversion efficiencies of 25.81-26.16% and fill factors of 82.52-86.69%). This indicates that the glass powder of the present invention can achieve good silver-silicon ohmic contact under conventional sintering processes, and its initial photoelectric performance is comparable to or slightly better than that of existing technologies. Notably, Example 3 has the highest conversion efficiency (26.13%) and fill factor (86.54%) among all groups, while maintaining a low series resistance (1.26 mΩ). This demonstrates that through component optimization and dual modification, not only was the initial conductivity not compromised, but the improved interface wettability and silver solubility further reduced contact losses.

[0067] Acetic acid vapor aging tests can effectively simulate the continuous corrosive effect of acetic acid generated by the degradation of EVA film on electrodes during the service life of photovoltaic modules. After accelerated aging with acetic acid vapor, the efficiency degradation rate of Examples 1-3 was only 2.9-4.7%, and the series resistance increase rate was 97-145%; while the efficiency degradation rate of Comparative Examples 1-4 was as high as 14.3-53.1%, and the resistance increase rate was 393-1282%. The degradation rate of the Examples was much lower than that of all Comparative Examples, especially compared with the Comparative Examples with similar composition but no modification, the advantage was extremely prominent. Taking Example 3 and Comparative Example 4 as examples, their initial performance was comparable (conversion efficiency 26.13% vs. 26.16%, fill factor 86.54% vs. 86.69%), but after aging, the efficiency degradation of Example 3 was only 2.9%, while that of Comparative Example 4 was as high as 29.4%, and the resistance increase rate was 97% for Example 3 and 618% for Comparative Example 4, indicating that the TiO2 coating layer plays a decisive role in inhibiting acetic acid corrosion. Comparing Example 2 and Comparative Example 3, both are lead-based glasses. Although Comparative Example 3 was crystallized, it was not coated, resulting in an efficiency decrease of 53.1% and a resistance increase of 1282%. In contrast, Example 2 (crystallization + coating) showed an efficiency decrease of only 4.7% and a resistance increase of 145%, further verifying that the synergistic effect of dual protection from crystallization and coating is far superior to single crystallization modification.

[0068] In summary, this invention, through the synergistic approach of component regulation, controllable crystallization, and TiO2 surface coating, significantly enhances the glass powder's resistance to acetic acid corrosion while maintaining or even improving the initial photoelectric conversion efficiency. It effectively suppresses the degradation of series resistance during long-term service and significantly improves the aging resistance and reliability of photovoltaic cells. This effect cannot be achieved by a single modification method in the comparative examples, demonstrating the synergy and unpredictability of the technical solution of this invention. Therefore, it provides a practical glass powder solution for the long-term stable mass production of high-efficiency crystalline silicon cells such as PERC, TOPCon, and HJT.

[0069] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing high acid-resistant glass powder, characterized in that, It includes the following steps: 1) Mix the oxide raw materials to obtain a mixed powder; 2) The mixed powder is sequentially melted, quenched, and crushed to obtain amorphous glass micro powder; 3) Crystallize the amorphous glass powder to obtain crystallized glass powder; 4) A titanium dioxide coating layer is formed on the surface of crystallized glass powder using the sol-gel method to obtain high acid-resistant glass powder.

2. The preparation method according to claim 1, characterized in that, By mass fraction, the oxide raw material in step 1) comprises 5-35% Bi2O3, 5-45% B2O3, 0-50% TeO2, 0-45% PbO, 0-10% ZnO, 0-15% Al2O3, and 0-8% alkali metal oxides; The sum of the mass fractions of Bi2O3, B2O3, TeO2 and PbO is ≥60%.

3. The preparation method according to claim 2, characterized in that, The oxide raw material also includes functional additives, which include one or more of SiO2, MgO, CaO, BaO, SrO, Ga2O3, V2O5, P2O5 and Fe2O3.

4. The preparation method according to any one of claims 1 to 3, wherein the melting temperature in step 2) is 800 to 1300°C, the melting time is 1 to 3 hours, and the heating rate to the melting temperature is 5 to 20°C / min.

5. The preparation method according to claim 4, characterized in that, Step 2) The particle size D of the amorphous glass micro powder 50 It is 1~2μm.

6. The preparation method according to claim 5, characterized in that, Step 3) The crystallization treatment temperature is 380~500℃, the crystallization treatment time is 6~10h, and the heating rate to the crystallization treatment temperature is 3~6℃ / min.

7. The preparation method according to claim 5 or 6, characterized in that, Step 4) The thickness of the titanium dioxide coating layer is 10~80nm.

8. The high acid-resistant glass powder prepared by the preparation method according to any one of claims 1 to 7.

9. The application of the high acid-resistant glass powder according to claim 8 in photovoltaic silver paste.